Meriahnya Raya UMPSA, more than 1,500 university members celebrate Aidilfitri - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 14 April 2025 – A lively and warm atmosphere was clearly visible on the faces of more than 1,500 members of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) who gathered at the UMPSA Pekan Multipurpose Hall in conjunction with the University-level Aidilfitri Celebration Ceremony today.